Structure of the nuclear exosome captured on a maturing preribosome - Schuller, Jan Michael; Falk, Sebastian; Fromm, Lisa; Hurt, Ed; Conti, Elena (Science, 2018)
The RNA exosome captured in action - The RNA exosome, a major RNA degradation machine, processes ribosomal RNA (rRNA) precursors and is directly coupled to the protein synthesis machine, the ribosome. Using cryo-electron microscopy, Schuller et al. investigated the structure of the precursor large ribosomal subunit from yeast with unprocessed rRNA in complex with the RNA exosome. The structure captures a snapshot of two molecular machines transiently interacting and explains how the RNA exosome acts on an authentic physiological substrate and remodels the large subunit during ribosome maturation. - Science, this issue p. 219 - The RNA exosome complex processes and degrades a wide range of transcripts, including ribosomal RNAs (rRNAs). We used cryo-electron microscopy to visualize the yeast nuclear exosome holocomplex captured on a precursor large ribosomal subunit (pre-60S) during 7S-to-5.8S rRNA processing. The cofactors of the nuclear exosome are sandwiched between the ribonuclease core complex (Exo-10) and the remodeled “foot” structure of the pre-60S particle, which harbors the 5.8S rRNA precursor. The exosome-associated helicase Mtr4 recognizes the preribosomal substrate by docking to specific sites on the 25S rRNA, captures the 3′ extension of the 5.8S rRNA, and channels it toward Exo-10. The structure elucidates how the exosome forms a structural and functional unit together with its massive pre-60S substrate to process rRNA during ribosome maturation. - The exosome forms a single structural and functional unit with its preribosomal substrate to catalyze ribosomal RNA processing and ribosome maturation. - The exosome forms a single structural and functional unit with its preribosomal substrate to catalyze ribosomal RNA processing and ribosome maturation.
Gesehen am 27.08.2019